1996
DOI: 10.2134/jeq1996.00472425002500030005x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nonpoint‐Source Pollution Using GIS and Numerical Models

Abstract: A geographic information system (GIS) was utilized to apply a modified DRASTIC method to the assessment of ground water contamination sensitivity in Goshen County, Wyoming. Several basic environmental characteristics, identified as influencing contaminant transport through the vadose zone to groundwater systems, were mapped, automated, and analyzed. These characteristics include: depth to groundwater, net recharge, hydrogeologic setting, vadose zone soil properties, land surface slope, and saturated hydraulic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 10 publications
(7 reference statements)
1
22
0
1
Order By: Relevance
“…DRASTIC model which is an overlay/index method (Vrba and Zaporotec, 1994;USEPA, 1993;Zhang et al, 1996) was developed by US/ EPA to be the standardized method for groundwater vulnerability assessment. DRASTIC can be categorized into 2 steps: (1) hydrogeology setting classification and (2) scoring method (Ckakraborty S et al, 2007).…”
Section: Assessment Of Aquifer Vulnerability With the Drastic Modelmentioning
confidence: 99%
“…DRASTIC model which is an overlay/index method (Vrba and Zaporotec, 1994;USEPA, 1993;Zhang et al, 1996) was developed by US/ EPA to be the standardized method for groundwater vulnerability assessment. DRASTIC can be categorized into 2 steps: (1) hydrogeology setting classification and (2) scoring method (Ckakraborty S et al, 2007).…”
Section: Assessment Of Aquifer Vulnerability With the Drastic Modelmentioning
confidence: 99%
“…The output data from this modeling were the cumulative water flux recharge to groundwater table since the start time of simulation, total amount of water in the soil, cumulative amount of solute leached to the groundwater since the start time of the simulation and the start time of groundwater pollution. The calculations showed that the contamination reached its maximum level in sandy soils much sooner than in clay soils (Zhang et al 1996).…”
Section: Gleams (Groundwater Loading Effects Of Agricultural Managemementioning
confidence: 94%
“…A geographic information system (GIS) with the DRASTIC model was used by Zhang et al (1996) to study the potential contamination of the groundwater in this regionandto understand which areas are more likely to become polluted considering the human activities on the land surface.The most sensitive locations were the areas near the streams, rivers and lakes. Also, the locations with shallow water tables and deep saturated layers of soil and soils with very high porosity were classified as highly sensitive.…”
Section: Gleams (Groundwater Loading Effects Of Agricultural Managemementioning
confidence: 99%
See 1 more Smart Citation
“…These include process based methods, statistical methods, and overlay/index methods [25,26]. The process based methods use simulation models (i.e., SWAT [27], HSPF [28], and GLEAMS [29]) to simulate contaminant transport [22].…”
Section: Drastic To Estimate Aquifer Vulnerabilitymentioning
confidence: 99%